Bidirectional Control of Alcohol-drinking Behaviors Through Locus Coeruleus Optoactivation. (1st September 2020) - Deal, Alex L.; Bass, Caroline E.; Grinevich, Valentina P.; Delbono, Osvaldo; Bonin, Keith D.; Weiner, Jeff L.; Budygin, Evgeny A.
Highlights: Alcohol-drinking behaviors can be controlled through LC optostimulation. Tonic stimulation during a drinking session results in increased alcohol intake. Phasic stimulation during a drinking session results in decreased alcohol intake. Tonic stimulation during an extinction trial does not alter alcohol-seeking behavior. Phasic stimulation during an extinction trial suppresses alcohol-seeking behavior. Abstract: The relationship between stress and alcohol-drinking behaviors has been intensively explored; however, neuronal substrates and neurotransmitter dynamics responsible for a causal link between these conditions are still unclear. Here, we optogenetically manipulated locus coeruleus (LC) norepinephrine (NE) activity by applying distinct stimulation protocols in order to explore how phasic and tonic NE release dynamics control alcohol-drinking behaviors. Our results clearly demonstrate contrasting behavioral consequences of LC-NE circuitry activation during low and high frequency stimulation. Specifically, applying tonic stimulation during a standard operant drinking session resulted in increased intake, while phasic stimulation decreased this measure. Furthermore, stimulation during extinction probe trials, when the lever press response was not reinforced, did not significantly alter alcohol-seeking behavior if a tonic pattern was applied. However, phasic stimulation substantially suppressed the number of lever presses, indicating decreased alcohol seeking under the same experimental condition. Given the well-established correlative link between stress and increased alcohol consumption, here we provide the first evidence that tonic LC-NE activity plays a causal role in stress-associated increases in drinking.